Pelatihan dan Pendampingan Pencatatan Keuangan Menggunakan Aplikasi Buku Warung di BUMDesa Mattiro Uleng, Kabupaten Pangkep: Pengabdian - Nur Halim; Pahrul; Mahmuddin; Nurhayani; Kemalasari, Andi Anggi (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This Community Service Activity (PKM) was driven by the urgent need to improve the accountability and efficiency of the financial management of the Mattiro Uleng Village-Owned Enterprise (BUMDesa) in Pangkep Regency. The focus of the intervention was on training and assistance in digital financial recording using the Buku Warung application as a practical solution. The main problems identified are the BUMDesa's dependence on manual bookkeeping, which is prone to errors, the inability to produce reliable financial reports, and a lack of transparency, which significantly hinders the sustainability of village business units. The PKM implementation method included four stages: comprehensive assessment, digital awareness socialization, hands-on training on the Buku Warung application, and measurable mentoring and evaluation through pre-tests and post-tests on 25 BUMDesa administrators. The material emphasized key features such as daily transaction recording, expenditure categorization, and digital accounts receivable/payable management. The evaluation results showed a significant increase in the average knowledge score of participants by 52.7 points (from 35.0 to 87.7), indicating successful technology adoption. This improvement proves that the adoption of user-friendly digital tools is very effective in transforming financial literacy and practices at the village level, so that BUMDesa Mattiro Uleng is expected to be able to achieve a higher level of transparency and accountability.